The impact of decentralization on regional development - شمع, م.م.مصطفى جليل ابراهيم (Journal of Planner and Development, 2007)
As regional development, as a matter of course, poses a number of systemic, scientific and political problems. While the issue of development is primarily at the national level to the limits of World War II in the industrialized world and to the 1960s borders in most Third World countries, the increasing awareness of regional disparities has led to the regional issue Were taken into consideration in the early 1960s and 1970s in most industrialized and developing countries alike. The local issue was only introduced in the early 1980s. The awareness of regional disparities and the fact that the regions do not have the same potential and that some regions have the resources to enable them to develop, grow and develop, unlike other regions that can not secure even their basic and urgent needs. The question of regional development started gradually in various economic development plans. The question of regionalization and the complexity of the concept of development and its concepts and methods and given the narrowness of this area to ask the various aspects will be limited in this research to address some aspects of the issue only the other was at the public and theoretical level.